(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this study was to look at the present research on yellow fungus. A growing number of academic publications in this area fuels interest in this subject. However, there still needs to be more quantitative data on this subject. The primary goal of this study was to compile research on the yellow fungus published in Web of Science-indexed publications between 1916 and June 6, 2021. The scientometric technique, a quantitative analysis of publication patterns, was employed for this research. The findings revealed a steady rise in research, with a significant increase beginning in 1991. A total of 2704 papers were published in 1056 journals, with an average of 22.36 percent citations per document. The highly cited papers were mostly found in WoS databases in Q1 category journals. Most of the published collaborative papers came from the United States, America, China, and other affluent countries; several developing countries also contributed. The pattern of authorship revealed an interdisciplinary and collaborative approach among scholars. Multiple Correspondence Analysis Conceptual Structure: Map-methods of Author's Keyword This scientometric study may help academics and funding organisations and policymakers worldwide.